Determining post-orthognathic surgery profile: A validation study on the potential of modified chin point as a reliable predictor - Pradeep Singh; Huijun Han; Heng Zhang; Richard Tai‑Chiu Hsung; Yifan Lin; Deepal Haresh Ajmera; Yiu Yan Leung; Lifeng Zhu; Congyi Zhang; Min Gu (PLoS ONE, 2025)
Objectives To investigate the validity of the modified chin point (MCP) as a reliable predictor for post-orthognathic surgery profile. Materials and methods 136 three-dimensional (3D) facial images from 68 patients (28 males and 40 females; mean age 24.6 ± 5.3 years) were collected. An artificial intelligence (AI)-assisted in-house software program was developed to automatically localize landmarks, compute the MCP, and perform automated distance measurements. The Steiner’s S line and Ricketts’ E line were computed for each scan to assess lip positioning relative to the reference lines. Validity was established by comparing MCP measurements to those from the actual chin point (ACP). Results No significant differences (p > 0.01) were observed in upper lip (UL) and lower lip (LL) positions between post-surgery ACP and MCP. Mean error (ME) and mean absolute error (MAE) for UL and LL positions in relation to ‘S’ and ‘E’ lines were generally small. Strong positive correlations were observed between ACP and MCP variables for UL measurements, while moderate positive correlations were observed for LL measurements for both ‘S’ and ‘E’ lines. Additionally, MCP-based post-surgery aesthetic lip positions did not differ significantly (p > 0.01) across genders. Conclusions This study provides evidence supporting MCP’s effectiveness in guiding aesthetic lip positioning in patients undergoing orthognathic surgery (OS). MCP is reliable and consistent in estimating post-surgery UL position and moderately reliable in estimating post-surgery LL position, validating its use as a predictor for the post-orthognathic surgery profile. Clinical significance The MCP-based prediction model can be easily incorporated into pre-surgical planning, allowing orthognathic surgeons and orthodontists to make appropriate adjustments to treatment plans, ensuring optimal treatment outcomes.